ELN iMDS flow working group validation of the monocyte assay for chronic myelomonocytic leukemia diagnosis by flow cytometry. Issue 1 (30th December 2021) - Wagner‐Ballon, Orianne; Bettelheim, Peter; Lauf, Jeroen; Bellos, Frauke; Della Porta, Matteo; Travaglino, Erica; Subira, Dolores; Lopez, Irene Nuevo; Tarfi, Sihem; Westers, Theresia M.; Johansson, Ulrika; Psarra, Katherina; et al.
Abstract: Background: It was proposed that peripheral blood (PB) monocyte profiles evaluated by flow cytometry, called "monocyte assay, " could rapidly and efficiently distinguish chronic myelomonocytic leukemia (CMML) from other causes of monocytosis by highlighting an increase in the classical monocyte (cMo) fraction above 94%. However, the robustness of this assay requires a large multicenter validation and the assessment of its feasibility on bone marrow (BM) samples, as some centers may not have access to PB. Methods: PB and/or BM samples from patients displaying monocytosis were assessed with the "monocyte assay" by 10 ELN iMDS Flow working group centers with harmonized protocols. The corresponding files were reanalyzed in a blind fashion and the cMo percentages obtained by both analyses were compared. Confirmed diagnoses were collected when available. Results: The comparison between cMo percentages from 267 PB files showed a good global significant correlation ( r = 0.88) with no bias. Confirmed diagnoses, available for 212 patients, achieved a 94% sensitivity and an 84% specificity. Hence, 95/101 CMML patients displayed cMo ≥94% while cMo <94% was observed in 83/99 patients with reactive monocytosis and in 10/12 patients with myeloproliferative neoplasms (MPN) with monocytosis. The established Receiver Operator Curve again provided a 94% cut‐off value of cMo. The 117 BM files reanalysis led to an 87% sensitivity and an 80% specificity, with excellent correlation between the 43 paired samples to PB. Conclusions: This ELN multicenter study demonstrates the robustness of the monocyte assay with only limited variability of cMo percentages, validates the 94% cutoff value, confirms its high sensitivity and specificity in PB and finally, also confirms the possibility of its use in BM samples.